Sistema web de monitoreo de aves de la provincia de Cotopaxi (SIMA). - Cajas Vega, Carmen Maribel (2019)
In the Cotopaxi province, this can be evidenced that there is a refusal of taxonomic digital records from birds, the data about bird species are not available to all the interested public. In front to this need is proposed the development of a Web System that presents to the world the different birds species, which keep their habitat in the Cotopaxi province, as well as the scientific information related with their taxonomy. For the development of the technological proposal has been used a set of process management from software development among that the IEEE 830 for the specification of software requirements. The SCRUM methodology is been applied, because it allow the rapid and reliable development of the application. The PHP development methods were used to determine the programming environment and MySql are used to build the database. The dataset used to monitor the birds correspond to information got since the year 2014 to the present, which was collected by students and teachers of the Career at Ecotourism, who have contributed to the development of this project. As the result is pretended for getting a reliable website interface that could serve like a tool of helping by interested in the study from birds, their composition and scientific information, which will be presented through web forms by determining the location of this species type into the Cotopaxi province and its scientific information. It is concluded that this type of computer applications contribute to the development of research processes, which the results of their studies can be made known through the Internet and its applications use.